Electronic Transport via Proteins. (25th September 2014) - Amdursky, Nadav; Marchak, Debora; Sepunaru, Lior; Pecht, Israel; Sheves, Mordechai; Cahen, David
<x xml:space="preserve">Abstract</x> A central vision in molecular electronics is the creation of devices with functional molecular components that may provide unique properties. Proteins are attractive candidates for this purpose, as they have specific physical (optical, electrical) and chemical (selective binding, self‐assembly) functions and offer a myriad of possibilities for (bio‐)chemical modification. This Progress Report focuses on proteins as potential building components for future bioelectronic devices as they are quite efficient electronic conductors, compared with saturated organic molecules. The report addresses several questions: how general is this behavior; how does protein conduction compare with that of saturated and conjugated molecules; and what mechanisms enable efficient conduction across these large molecules? To answer these questions results of nanometer‐scale and macroscopic electronic transport measurements across a range of organic molecules and proteins are compiled and analyzed, from single/few molecules to large molecular ensembles, and the influence of measurement methods on the results is considered. Generalizing, it is found that proteins conduct better than saturated molecules, and somewhat poorer than conjugated molecules. Significantly, the presence of cofactors (redox‐active or conjugated) in the protein enhances their conduction, but without an obvious advantage for natural electron transfer proteins. Most likely, the conduction mechanisms are hopping (at higher temperatures) and tunneling (below ca. 150–200 K).